(untitled) (Journal of Pharmaceutical Negative Results, 2022)
In the present study the comparative floral morphological investigation was done by 5 species of the family Apocynaceae from Kanyakumari District. The species are Adenium obesum (Forssk.) Roem. & Schult., Allamanda schottii Pohl, Kopsia fruticosa (Roxb.) A.DC., Pentalinon luteum (L.) B.F.Hansen & Wunderlin and Wrightia antidysenterica (L.) R.Br. A complete taxonomic account of each species has been given along with quantitative and qualitative characters. Flowers of 5 species studied here showed large variations in shape, color and size of different parts.